Investigating the ecology, diversity and distribution of cord-forming fungi in Great Britain - Wallis, K (2014)
Cord-forming fungi (CFF) are an assemblage of saprotrophic fungi which can use complex foraging organs of longitudinally arranged hyphae to join up disparate substrates in a patchy resource environment. Their importance to woodlands lies, mainly, in their ability to modify nutrient cycling and soil structure. Therefore, in order to enable woodlands to continue to thrive in terms of their health and ecosystem function, it is necessary to understand the factors contributing to the establishment, success and diversity of this group. Whilst work to date on CFF has focussed on their physiology and interactions in laboratory conditions, little work has been carried out on their taxonomy and establishment/presence in the field. The work in this thesis begins to address these crucial unanswered questions in CFF ecology. By carrying out investigations at a range of scales, from phylogenetic analysis to UK wide Species Distribution Modelling, this thesis reaches a number of surprising results with potentially important implications for woodland management. This is most evident in Chapter 3 where our hypothesis that fungal communities develop over time in plantations of different woodland ages was disproved, illustrating that even 13 years after planting, fungal communities in plantations on ex-agricultural land had not begun to reach those in established ASNW. These unexpected results continue into Chapter 4, where the thesis demonstrates that dominant canopy species has a greater impact on community composition than any other woodland factor. Chapter 5 continues this theme, by showing that removal of invasive species is not always beneficial for the cord-forming fungal communities, especially if it involves removing the woody substrate. The work described, detailed and analysed in this thesis has initiated further investigations, proposed changes to woodland management practices and laid the foundations for future work relating to CFF and their role and function in British woodlands.